The Effect Of Using English Song To Improve Students’ Pronunciation By 7th Grade At Smp Swasta Al Washliyah 27 Medan - Risma Yanti, Yulia Sari Harahap (CV. PUSDIKRA MITRA JAYA, 2022)
The objective of this research was to investigate the effectiveness of using English song in students’ pronunciation skill. This research was conducted to the second grade students of SMP Al Washliyah 27 Medan in academic year 2020/2021. In this research, a pre-experimental design was used by the writer which two classes and the total number of students 60. Sample of this research consisted of two classes. The sample was devided into two groups, the first group is 30 students (Grade VII A) which is the experimental group and the second group is 30 students (Grade VII B) which is control group. The experimental group was taught by using English song while the control group was taught without using English song. The writer used the instrument for collectingthe data was oral test. The result of the analysis showed that the t-observed (2.35), it was higher than the t-table (2.00) with the level of significant (0.05) and the degree of freedom (df) (58). In conclusion, the effectiveness of the use English song is very strong to improve the students’ pronunciation skill.